A synbiotics, long chain polyunsaturated fatty acids, and milk fat globule membranes supplemented formula modulates microbiota maturation and neurodevelopment. Issue 8 (August 2022) - Cerdó, Tomás; Ruíz, Alicia; Acuña, Inmaculada; Nieto-Ruiz, Ana; Diéguez, Estefanía; Sepúlveda-Valbuena, Natalia; Escudero-Marín, Mireia; García-Santos, Jose Antonio; García-Ricobaraza, María; Herrmann, Florian; Moreno-Muñoz, Jose Antonio; De Castellar, Roser; et al.
Summary: Background & aims: The critical window of concurrent developmental paths of the nervous system and gut microbiota in infancy provides an opportunity for nutritional interventions with potential health benefits later in life. Methods: We compared the dynamics of gut microbiota maturation and explored its association with neurodevelopment at 12 months and 4 years of age in 170 full-term healthy infants fed a standard formula (SF) or a new formula (EF) based on standard formula supplemented with synbiotics, long chain polyunsaturated fatty acids (LC-PUFA) and bovine milk fat globule membranes (MFGM), including a breastfed reference group (BF). Results: Using Dirichlet Multinomial Modelling, we characterized three microbial enterotypes (Mixed, anaerobic and aerobic profile; Bact, Bacteroides-dominant; Firm, Firmicutes-enriched) and identified a new enterotype dominated by an unidentified genus within Lachnospiraceae (U_Lach). Enterotypes were associated with age (Mixed with baseline, U_Lach with month 6, Bact and Firm with months 12 and 18). Trajectories or timely enterotype shifts in each infant were not random but strongly associated with type of feeding. Trajectories in SF shifted from initial Mixed to U_Lach, Bact or Firm at month. Microbiota maturation in EF split into a fast trajectory as in SF, and a slow trajectory with Mixed to U_Lach, Bact or Firm transitions at months 12 or 18, as in BF. EF infants with slow trajectories were more often in–home reared and born by vaginal delivery to mothers with pre-pregnancy lean BMI. At 12 months of age, language and expressive language scores were significantly higher in EF infants with fast trajectories than in BF. Neurodevelopmental outcomes were similar between EF infants with slow trajectories and BF at 12 months and 4 years of age. Conclusions: Feeding a synbiotics, LC-PUFA and MFGM supplemented formula in a specific infant environment promoted probiotic growth and retarded gut microbiota maturation with similar neurodevelopment outcomes to breastfed infants. Clinical trial registry number: NTC02094547.